Osmanlı Devleti'nde bilgi ve istatistik = : Data and statistics in the Ottoman Empire - İnalcık, Halil; Pamuk, Şevket (Devlet İstatistik Enstitüsü (Series) ;, 2000)
Partial table of contents [English language article titles]: Did the Ottomans use statistical methodology / Halil ♯ʻnalc♯łk; Quantitative data in the Ottoman tahrir (census) records / Mehmet ©z; Avar♯łz and cizye records / Oktay ©zel; Data on consumer prices and wages in Ottoman cities / ¿evket Pamuk; Ottoman population statistics and modernization after 1831 / Cem Behar; Nineteenth Century temettuat (revenue) censuses / Tevfik G©ơran; Quantification in the Ottoman state or the birth of modern statistics / Zafer Toprak; Nineteenth Century Ottoman foreign trade statistics / ¿evket Pamuk; Education and education statistics in the Ottoman Empire, 1839-1924 / Mehmet ©. Alkan; The Istanbul census dated 1301 Rumi (1885 A.D.) / Sel©ʹuk Ak¿in Somel; The first Ottoman statistical yearbook dated 1897 / Tevfik G©ơran.